What Do Primary Care Prediabetes Patients Need? A Baseline Assessment of Patients Engaging in A Technology-Enhanced Lifestyle Intervention. - M Kolb Jennifer; R. Kitos Nicole; Ramachandran Ambili; J. Lin Jenny; M. Mann Devin (Journal of Bioinformatics And Diabetes, 2014)
Objective: This study assessed the baseline knowledge, perceptions, attitudes and behaviors of prediabetes patients in order to tailor a new technology-enhanced primary care-based lifestyle modification intervention. Methods: Patients with a diagnosis of prediabetes were enrolled in a randomized, controlled pilot study, Avoiding Diabetes Thru Action Plan Targeting (ADAPT), a technology-based intervention to promote action plan discussions around patient-selected behavior change goals. Results: A total of 54 adults (82% female) were enrolled in the pilot study. Most (89%) had comorbid conditions and mean BMI was 36. Participants exhibited significant levels of diabetes risk knowledge and diabetes risk perception, as well as high levels of willingness to make changes to decrease diabetes risk. Number of daily steps was inversely correlated with perceived physical activity (r=-0.35082, p<0.001). Poorer scores on diet quality were inversely correlated with BMI. Conclusion: Participants in this sample demonstrated requisite levels of knowledge, self-efficacy, motivation and risk perception for effective behavior change. These data suggest that primary care-based prediabetes interventions can move beyond educational goals and focus on enhancing patients’ ability to select, plan and enact action plans.
Keywords: Type II Diabetes Mellitus